A Stystems Approach to small Group Interaction - L. Tubbs Stewart (American : MC Graw Hill, 2007)
The only book for Small Group Communication that integrates all important small group topics into a single comprehensive conceptual model, this text pioneered the systems approach for the group communication course. Each chapter begins with a brief preview, followed by a glossary of terms and a real life case study; the chapter text material is followed by several experiential exercises for skill development and two original readings.
Keywords: Team in the workplace; Small groups; Organizational behavior